2016
DOI: 10.1016/j.celrep.2016.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biological Compatibility with Host Alpha-Synuclein Influences Fibril Pathogenicity

Abstract: Summary The accumulation and propagation of misfolded α-Synuclein (α-Syn) is a central feature of Parkinson’s disease (PD) and other synucleinopathies. Molecular compatibility between a fibrillar seed and its native protein state is a major determinant of amyloid self-replication. We show that cross-seeded aggregation of human (Hu) and mouse (Ms) α-Syn is bidirectionally restricted. Although fibrils formed by Hu-Ms-α-Syn chimeric mutants can overcome this inhibition in cell-free systems, sequence homology poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
179
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 154 publications
(201 citation statements)
references
References 42 publications
(58 reference statements)
18
179
4
Order By: Relevance
“…Our results indicated that larger o-αSyn species lost their ability to reduce synapsins when introduced into SNCA-null neurons lacking αSyn, whereas smaller o-αSyn assemblies did not depend on endogenous αSyn to lower synapsins, reminiscent of prion-like mechanisms. In agreement with earlier reports (35,40,62), these findings therefore suggested the presence of different functional conformers of αSyn with species requiring template assembly and others that did not. On the one hand, the fact that both αSyn aggregates trigger the same cellular change is surprising, as one would perhaps predict differential alterations in neuronal biology induced by each species.…”
Section: Dependence On Endogenous αSyn For Exogenous O-αsyn To Inducesupporting
confidence: 92%
“…Our results indicated that larger o-αSyn species lost their ability to reduce synapsins when introduced into SNCA-null neurons lacking αSyn, whereas smaller o-αSyn assemblies did not depend on endogenous αSyn to lower synapsins, reminiscent of prion-like mechanisms. In agreement with earlier reports (35,40,62), these findings therefore suggested the presence of different functional conformers of αSyn with species requiring template assembly and others that did not. On the one hand, the fact that both αSyn aggregates trigger the same cellular change is surprising, as one would perhaps predict differential alterations in neuronal biology induced by each species.…”
Section: Dependence On Endogenous αSyn For Exogenous O-αsyn To Inducesupporting
confidence: 92%
“…When aSyn fibrils have formed, the ThT assay should result in readings 20–100 folder higher for human aSyn PFFs as compared to human aSyn monomers (Figure 5A). Human aSyn PFFs will also result in higher levels of ThT than murine aSyn PFFs, leading to greater subtlety in differences between monomers and PFFs in murine aSyn as compared to human aSyn [51. A protocol for the ThT assay can also be found in Appendix A.…”
Section: Validation Of Proper Alpha-synuclein Pre-formed Fibril Formamentioning
confidence: 99%
“…Therefore, investigators should remember to use the proposed quality control methods in Figure 5A–G as general pass/fail criteria whereby failure suggests the need to remake the PFFs and success suggests likely (but not guaranteed) pathology when introduced in vivo. For pilot studies, analysis at 30 dpi is generally enough time to induce robust pS129 pathology in the rat [34] and mouse [51] brain after striatal injection, although rates of pathology may differ based on the species of aSyn PFFs, the rodent strain, the target structure, and the aSyn PFF dose, among other factors.…”
Section: Validation Of Proper Alpha-synuclein Pre-formed Fibril Formamentioning
confidence: 99%
See 2 more Smart Citations